Transformational Bureaucratic Leadership Model to Support National Defense Policy in Indonesia - Sjafrie Sjamsoeddin; Purnomo Yusgiantoro; Herlina Juni Risma Saragih; Budi Susilo Soepandji (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
Globalization has produced a complex strategic environment, posting a dynamic threat to national security. In this case, a strategic form of leadership becomes important in running a country, especially in the context of national defense. The purpose of this article is to reveal the bureaucratic leadership style that can function as a form of strategic leadership in national defense policy. Based on the literature study method, it was found that a transformational bureaucratic leadership model can be a form of strategic leadership in National Defense Policy in Indonesia. Leadership transformation is carried out through competency development in the form of superior leadership abilities and attitudes that are in accordance with the needs of the times. With this competence, bureaucratic leaders are expected to perform their leadership duties proportionately and handle any problems that may arise in their organization. The guardian leadership that can motivate, encourage, and serve as an example for their subordinates will be crucial in the realization of the bureaucratic leadership style to support national defense policy. Characteristics of a leader with honor, creativity, discipline, motivation, anticipation, guardianship, spirit of nationalism and patriotism, and integrity will have a positive impact on the National Defense Policy. By combining breakthroughs with a type of continuous control, the division of specific tasks at specific organizational level, and Millennial HR’s involvement, a leadership approach will be able to explore the potential to produce organizational performance far above what has been achieved so far, in particular in Indonesian National Defense policy management.